Effect of Quality of Kraft Paper on the Physical Properties of Corrugated Fibreboard - Srinivasa Gopal, T.K.; Hridayanathan, C. (Fishery Technology, 2025)
Kraft paper that is used in the manufacture of corrugated tibreboard for fishery products collected from different fabricators in and around Kochi were evaluated for grammage, caliper, bursting strength, ring stiffness, tearing strength, tensile strength and elongation at break in machine and cross direction. It is observed that the bursting strength, tensile strength and ring stiffness are dependant and the tearing strength is independant of the virginity of the kraft paper.